2020
DOI: 10.1177/1046878120972458
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of the Skills and Attitudes Conveyed by Two Business Simulation Games in Pécs, Hungary

Abstract: Background. Business simulation games have been used since 1979 at the University of Pécs. Since 2000, two games have been taught: a green business simulation developed on site and known as BUSINESS SIMULATION CHALLENGE and the MULTINATIONAL MANAGEMENT GAME. In this research we report on a longitudinal study of the results of the two business simulations; and investigate the effects of the Green Business simulation. Method. This survey-based research included 329 students that completed a questionnaire on busi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
1
0
0
1
Order By: Relevance
“…Experiences from previous years (40%) and good orientation in financial statements (35%) were perceived by the students as the most important factors for reaching the highest index PI/EVA. Even in the partial analyses for each year during 2016-2021, it was found that the results do not differ significantly and can be agreed with the research study "Attitudes and skills of generations do not change over time and the skills and knowledge that simulations convey can be considered constant throughout the period" [42].…”
Section: Discussionsupporting
confidence: 78%
“…Experiences from previous years (40%) and good orientation in financial statements (35%) were perceived by the students as the most important factors for reaching the highest index PI/EVA. Even in the partial analyses for each year during 2016-2021, it was found that the results do not differ significantly and can be agreed with the research study "Attitudes and skills of generations do not change over time and the skills and knowledge that simulations convey can be considered constant throughout the period" [42].…”
Section: Discussionsupporting
confidence: 78%
“…A pesar de haber recibido críticas (Bogost, 2011) por tratarse de una especie de "cajón de sastre" en el que todo cabe, precisamente quizás por eso ha sido uno de esos términos "afortunados" que han calado entre diferentes públicos (tanto académicos como no académicos) y sectores (no sólo el sector educativo sino también la industria del entretenimiento, el área de la salud, el marketing, y el ámbito empresarial en su conjunto). Este afán aglutinador del término gamificación, así como la juventud del campo de estudio, ha provocado ciertas controversias y solapes con otros términos como los juegos serios o serious games (SGs) (Alexiou, Schippers, Oshri, y Angelopoulos, 2020), el game-based learning (GBL) (Hooshyar et al, 2020), los educational games (Yu, Gao, y Wang, 2020) o los simulation games (Kiss, y Schmuck, 2020).…”
Section: Concepto Y Definición De Gamificaciónunclassified